Empowering Rural Futures: A Penta Helix Approach to Agricultural Development and Village Autonomy in Tana Tidung - Kurniasih, Nia; Syahran, Syahran; Nawir, Daud; Sintia, Riska Ananda; Nizhamuddin, Nizhamuddin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2025)
Rural communities across the globe confront multifaceted challenges in attaining sustainable autonomy, encompassing economic, social, and institutional dimensions. This study critically examines the agricultural potential, institutional robustness, and social capital within Tana Tidung Regency, Indonesia, and devises a Pentahelix-based strategic framework to harness these assets optimally. Employing a descriptive analytical methodology, the research reveals that villages in Tana Tidung are endowed with substantial economic resources—spanning agriculture, livestock, and plantation sectors—complemented by competent human capital, resilient institutions, vibrant social networks, and accessible health services. To expedite the realization of village self-reliance, the study advocates for diversified economic pathways, customized educational and vocational training programs, alongside comprehensive infrastructural enhancements encompassing transportation, electrification, telecommunications, and market connectivity. Integral to this approach is the cultivation of synergistic partnerships between village entities and external actors, including private enterprises and non-governmental organizations. Further strategic imperatives entail the implementation of non-formal educational initiatives, expansion of digital inclusivity, women’s economic empowerment, and capacity building of village officials in governance, fiscal stewardship, leadership, and policy execution. Reinforcing financial transparency, nurturing heterogeneous community organizations, facilitating periodic socio-cultural engagements, and augmenting healthcare infrastructure and outreach are equally pivotal. This holistic and integrative model proffers a scalable blueprint conducive to sustainable rural development and fortified village autonomy.